Register Now

222-9+11+12:2*14+14 = ? ( )

## Toán Lớp 8: tìm x: a, 3(2x-1) . (3x+1) + (2x-3) . (9x-1)= 0 b, (x+2) . (x ² – 2x +4 ) – x(x ² +2 ) = 5 c, 3(x+2) ² + (2x – 1) ² -7(x+3)(x+3) =

Toán Lớp 8: tìm x:
a, 3(2x-1) . (3x+1) + (2x-3) . (9x-1)= 0
b, (x+2) . (x ² – 2x +4 ) – x(x ² +2 ) = 5
c, 3(x+2) ² + (2x – 1) ² -7(x+3)(x+3) = 36
d, (x+3)(x+2) – (x-2)(x+5) = 6
e, 3(2x-1)(3x-1) – (2x-3)(9x-1) = 0

## Comments ( 1 )

1. Giải đáp + Lời giải và giải thích chi tiết:
a) 3(2x-1)(3x+1)+(2x-3)(9x-1)=0
<=>3(6x^2+2x-3x-1)+18x^2-2x-27x+3=0
<=>18x^2+6x-9x-3+18x^2-2x-27x+3=0
<=>36x^2-32x=0
<=> 4x(9x – 8) = 0
<=>$$\left[ \begin{array}{l}4x=0\\9x-8=0\end{array} \right.$$ <=>$$\left[ \begin{array}{l}x=0\\x=\dfrac{8}{9}\end{array} \right.$$
Vậy S={0;8/9}
b) (x+2)(x^2-2x+4)-x(x^2+2)=5
<=>x^3+8-x^3-2x=5
<=> 8-2x=5
<=>2x=3
<=>x=3/2
Vậy S={3/2}
c) 3(x+2)^2+(2x-1)^2-7(x+3)(x+3)=36
<=>3(x^2+4x+4)+(4x^2-4x+1)-7(x^2+6x+9)=36
<=>3x^2+12x+12+4x^2-4x+1-7x^2-42x-63=36
<=>-34x-50=36
<=>-34x=86
<=>x=-86/34=-43/17
Vậy S={-43/17}
d) (x+3)(x+2)-(x-2)(x+5)=6
<=>x^2+5x+6-(x^2+5x-2x-10)=6
<=>x^2+5x+6-x^2-5x+2x+10=6
<=>2x+16=6
<=>2x=-10
<=>x=-5
Vậy S={-5}
e) 3(2x-1)(3x-1)-(2x-3)(9x-1)=0
<=>3(6x^2-2x-3x+1)-(18x^2-2x-27x+3)=0
<=>18x^2-6x-9x+3-18x^2+2x+27x-3=0
<=>14x=0<=>x=0
Vậy S={0}.